Foreign aid volatility and lifelong learning - Simplice Asongu; Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2019)
This paper has put a demand-side empirical structure to the hypothesis that foreign aid volatility adversely affects choices to lifelong learning in recipient countries. Lifelong learning is measured as the combined knowledge acquired during primary, secondary and tertiary educational enrolments. Three types of aggregate foreign aid volatilities are computed in a twofold manner: baseline standard deviations and standard errors (standard deviations of residuals after first-order autoregressive processes). An endogeneity robust system GMM empirical strategy is employed. The findings broadly show that foreign aid volatility does not adversely affect the demand-side choices of lifelong learning in Africa. As a policy implication, when faced with aid uncertainty, the demand for education would increase. This may be explained by the need for more selfreliance in order to mitigate income risks or/and the use of education as means of coping with uncertainty. More policy implications are discussed.
Keywords: I20; I28; F35; O55; P16; 330; Lifelong learning; Foreign aid; Development; Africa